Identifying early markers of synaptic dysfunction in a mouse model of tauopathy: Molecular and cell biology/synaptic disruption. (7th December 2020) - Meftah, Soraya; Witton, Jonathan; Cavallini, Annalisa; Murray, Tracey K.; Jankowski, Lukasz; Bose, Suchira; Ashby, Michael; Brown, Jonathan T.
Abstract: Background: Synaptic degeneration is currently the best correlate of cognitive decline in Alzheimer's Disease. Tau pathology, one of the hallmarks of the disease, correlates well with synaptic degeneration and has been shown to abnormally mislocate to synapses in the disease. This process is thought to induce changes in the activity, number and structure of synapses leading to widespread synaptic dysfunction prior to neurodegeneration. However, the precise mechanistic and functional changes are unclear. Therefore, identifying early markers of synaptic dysfunction will provide novel insights into mechanistic changes that precede neurodegeneration and underlie symptomatic onset in tauopathy. Method: To investigate this, we used a multi‐faceted approach to characterise synaptic changes in the somatosensory cortex of the rTg4510 model of tauopathy, just prior (5.5 months) and post (7.5 months) neurodegeneration. Synaptic, neuronal and network function was assessed using in vitro and in vivo whole‐cell patch clamp electrophysiology, which allows for post‐hoc complementary analysis of morphology in recorded neurons. Protein expression of glutamatergic receptors, synaptic markers and tau were also quantified in crude synaptosomes by western blot. Result: Prior to neurodegeneration, glutamatergic synaptic function was altered (decreased NMDA:AMPA ratio) and dendritic structure was altered (increased branching proximal to soma). Protein expression of synaptic markers and AMPA receptors were significantly decreased in the somatosensory cortex. Post neurodegeneration, a reduction in AMPA mediated synaptic communication was observed (sEPSC frequency), matched with a progressive decrease in AMPA receptor expression and the synaptic marker, PSD95. Conclusion: Our results suggest that glutamatergic signalling is altered differently at the regional and single cell level just prior to neurodegeneration. For example, whilst regional AMPA receptor expression decreases pre‐neurodegeneration in the brain, it appears to be partially compensated for functionally within single neurons and the larger network. We predict that there may be a degree of compensation within the network, which when past a threshold leads to widescale network alterations and symptomatic changes. Deconstructing how functional compensation occurs in the brain in neurodegenerative diseases will shed light on how to delay symptomatic onset in tauopathies.